RNase III-Binding-mRNAs Revealed Novel Complementary Transcripts in Streptomyces - Šetinová, Dita; Šmídová, Klára; Pohl, Pavel; Musić, Inesa; Bobek, Jan (Frontiers in Microbiology, 2018)
cis-Antisense RNAs (asRNAs) provide very simple and effective gene expression control due to the perfect complementarity between regulated and regulatory transcripts. In Streptomyces, the antibiotic-producing clade, the antisense control system is not yet understood, although it might direct the organism’s complex development. Initial studies in Streptomyces have found a number of asRNAs. Apart from this, hundreds of mRNAs have been shown to bind RNase III, the double strand-specific endoribonuclease. In this study, we tested 17 mRNAs that have been previously co-precipitated with RNase III for antisense expression. Our RACE mapping showed that all of these mRNAs possess cognate asRNA. Additional tests for antisense expression uncovered as-adpA, as-rnc, as3983, as-sigB, as-sigH, and as-sigR RNAs. Northern blots detected the expression profiles of 18 novel transcripts. Noteworthy, we also found that only a minority of asRNAs respond to the absence of RNase III enzyme by increasing their cellular levels. Our findings suggest that antisense expression is widespread in Streptomyces, including genes of such important developmental regulators, as AdpA, RNase III, and sigma factors.